2015
DOI: 10.3389/fpls.2015.01019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a SUMO E2 Conjugating Enzyme Involved in Resistance to Clavibacter michiganensis Subsp. michiganensis in Solanum peruvianum, Through a Tomato Mottle Virus VIGS Assay

Abstract: Clavibacter michiganensis subsp. michiganensis (Cmm) causes bacterial wilt and canker of tomato. Currently, no Solanum lycopersicum resistant varieties are commercially available, but some degree of Cmm resistance has been identified in Solanum peruvianum. Previous research showed up-regulation of a SUMO E2 conjugating enzyme (SCEI) transcript in S. peruvianum compared to S. lycopersicum following infection with Cmm. In order to test the role of SCEI in resistance to Cmm, a fragment of SCEI from S. peruvianum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…It is noteworthy that the silencing efficiency for the phloem-specific RTM1 gene using Tu- RTM1 reached nearly 90%, highlighting the robustness and the usefulness of TuYV vectors. For a non-phloem specific gene ( CHLI1 ) the knockdown level obtained with the phloem-specific TuYV vector is in the same range (49–67%) as those obtained with several non-phloem specific VIGS systems (70% for a Potato virus X vector ( Ratcliff et al, 2001 ), 61–87% for TMV-based vectors ( Lacomme et al, 2003 ), 75–90% for TYMV-PDS ( Pflieger et al, 2008 ), 61% for a geminivirus Tomato mottle virus- chI I ( Esparza-Araiza et al, 2015 ) and 40–80% for a pararetrovirus Rice tungro baciliform virus- chl H ( Kant and Dasgupta, 2017 ). The paradoxical important reduction of non-phloem CHLI1 transcripts in plants infected with phloem-limited TuYV recombinants can be explained by the spread of the vsiRNAs, produced in infected phloem cells, into the surrounding cells, allowing the silencing process to extend beyond the sites of initiation, if not countered by the RSS P0 (see below).…”
Section: Discussionmentioning
confidence: 60%
“…It is noteworthy that the silencing efficiency for the phloem-specific RTM1 gene using Tu- RTM1 reached nearly 90%, highlighting the robustness and the usefulness of TuYV vectors. For a non-phloem specific gene ( CHLI1 ) the knockdown level obtained with the phloem-specific TuYV vector is in the same range (49–67%) as those obtained with several non-phloem specific VIGS systems (70% for a Potato virus X vector ( Ratcliff et al, 2001 ), 61–87% for TMV-based vectors ( Lacomme et al, 2003 ), 75–90% for TYMV-PDS ( Pflieger et al, 2008 ), 61% for a geminivirus Tomato mottle virus- chI I ( Esparza-Araiza et al, 2015 ) and 40–80% for a pararetrovirus Rice tungro baciliform virus- chl H ( Kant and Dasgupta, 2017 ). The paradoxical important reduction of non-phloem CHLI1 transcripts in plants infected with phloem-limited TuYV recombinants can be explained by the spread of the vsiRNAs, produced in infected phloem cells, into the surrounding cells, allowing the silencing process to extend beyond the sites of initiation, if not countered by the RSS P0 (see below).…”
Section: Discussionmentioning
confidence: 60%
“…In tomato, the SCE1-silenced plants were more susceptible to a bacterial disease caused by Clavibacter michiganensis subsp. michiganensis [47]. These findings indicate that sumoylation plays a protective role in stress responses of plants.…”
Section: Discussionmentioning
confidence: 69%
“…A recent study confirmed that the expression levels of the genes involved in the PAL pathway are upregulated in response to Cm infection [56]. Additionally, the silencing of the gene encoding SUMO E2-conjugating enzyme (SCEI) in plants leads to enhanced Cm colonization and a substantial increase in damaged tissues (4.5 times on average), reflecting the importance of SCEI for the innate immunity of S. peruvianum accession LA2172 [65].…”
Section: Identification and Verification Of Resistance-related Protei...mentioning
confidence: 80%